MoS2 nanosheet-coated CoS2 nanowire arrays on carbon cloth as three-dimensional electrodes for efficient electrocatalytic hydrogen evolution. Issue 45 (15th October 2015) - Huang, Jilin; Hou, Dongman; Zhou, Yucheng; Zhou, Weijia; Li, Guoqiang; Tang, Zhenghua; Li, Ligui; Chen, Shaowei
Abstract : MoS2 nanosheet-coated CoS2 nanowire arrays supported on carbon cloth exhibited excellent HER activity with an overpotential of −87 mV ( vs. RHE) at 10 mA cm −2 due to the synergistic interactions between MoS2 and CoS2 . Abstract : The design and engineering of low-cost and high-efficiency electrocatalysts for the hydrogen evolution reaction (HER) has attracted increasing interest in renewable energy research. Herein, MoS2 nanosheet-coated CoS2 nanowire arrays supported on carbon cloth (MoS2 /CoS2 /CC) were prepared by a two-step procedure that entailed the hydrothermal growth of Co(OH)2 nanowire arrays on carbon cloth followed by reaction with (NH4 )2 MoS4 to grow an overlayer of MoS2 nanosheets. Electrochemical studies showed that the obtained 3D electrode exhibited excellent HER activity with an overpotential of −87 mV at 10 mA cm −2, a small Tafel slope of 73.4 mV dec −1 and prominent electrochemical durability. The results presented herein may offer a new methodology for the design and engineering of effective multilevel structured catalysts for the HER based on earth-abundant components.